Estudo farmacológico da Vitex agnus-castus L (ação antinociceptiva e toxicidade aguda do extrato aquoso) - Oliveira, José Carlos Martins de (2005)
Since ancient times men have been using plants as food, and also for medicine preparation, for its necessity to cure diseases or alleviate pains. Innumerable scientific studies have been carried out aiming to validate popular information about the use of medicinal plants. The importance of this study is real for the following reasons: pain is one of the most complex problems that affect human beings, the costs of industrialized medicines are prohibitive, and the fact that Brazil as a developing country has 60% of the industrialized remedies being consumed by only 23% of the Brazilian population. This research may reduce costs of public health programs and consequently, be a way of extending the number of benefits and users of these programs. The present work of experimental research aimed at evaluating antinociceptive action and acute toxicity of the watery extract taken from leaves of Vitex agnuscastus L, known, in caatinga of the state of Sergipe-Br, as chasteberry, a very common plant in this area, used for pain relief through the use of its leaves. The anti-nociceptive effect of the watery extract of Vitex agnus-castus leaves was tested through the experimental models of nociception in mice. The hydrous extract (200 and 400mg/Kg) decreased the acid nociception, produced by the ascetic acid (0.6%), in 46.5% and 70.7% and increased latency period (s) of the mice in the hot plate test. In the formalin test (1%) the extract (400mg/Kg) reduced the nociception in 59.6%. The anti-nociceptive effect of the plant was reverted by naloxone (5mg/Kg). The hydrous extract of V. agnus-castus did not have reach DL50 until the dose of 5g/Kg, indicating low acute toxicity in mice. The anti-nociceptive effect of this plant is associated with the opioid system.